Acadia as spotted by the Dictionnaire des Francophones or collaborative digital lexicography as a tool to explore otherness. (Ponti/Ponts. Langues, littératures, civilisations des pays francophone, 2025)
In this paper, we intend to approach the notion of otherness from the angle of diatopic variation and, more specifically, the lexical variety of Acadian French. To do this, we’ll be looking at the Dictionnaire des Francophones, and in particular at the phraseological units used in Acadian French and inventoried in this brand-new collaborative digital dictionary. So, we will present the DDF and the contribution of its Canadian partners, we will define its innovative knowledge engineering modeling. Finally, we’ll focus on idioms, according to the model proposed by LEC. We will aim to show how idioms contribute to show the linguistic vitality and identity of this province, by attesting to its otherness.
Keywords: Otherness; phraseology; Acadian idioms; diatopic variation; digital and collaborative lexicography; Dictionnaire des francophones